Assessment of ultrasound effectiveness for the diagnostics of common bile duct diseases complicated by obstructive jaundice - Boyko, Valeriy Vladimirovich; Avdosyev, Yuriy Vladimirovich; Sochnieva, Anastasiia Lvovna; Yevtushenko, Denys Oleksandrovych (Харківська обласна громадська організація "Культура здоров'я", 2019)
Ultrasound is the first-priority screening test in the diagnostics of common bile duct diseases that enables the differentiation of jaundice genesis and determination of indications and contraindications for further non-invasive and invasive tests. The aim of research is to determine the effectiveness of ultrasound for the diagnostics of common bile duct diseases complicated by obstructive jaundice (OJ).
Keywords: jaundice; ultrasound; bile; bile ducts; disease; screening test